Do Spitzenkandidaten really make a difference? An experiment on the effectiveness of personalized European Parliament election campaigns. (December 2020) - Gattermann, Katjana; Marquart, Franziska
This article investigates the impact of pan-European candidates in European Parliament election campaigns. It focusses on the two 2019 nominees for the European Greens, who were Dutch and German, respectively. We conducted a pre-registered experiment in the Netherlands and Germany in early April 2019 to test the effects of (non-)personalized campaign posters on (a) turnout intention and (b) vote intention for the Greens alongside possible mediating effects of campaign and candidate evaluations. Our results suggest that while personalized campaigns as opposed to non-personalized campaigns may not matter per se for turnout and vote intention, individual candidates can make a difference in European elections, particularly with respect to vote intention. As such, the results have important implications for our understanding of European Parliament election campaigns.